A new skink of the genus Sphenomorphus Fitzinger, 1843 (Squamata: Scincidae) from Hon Ba Nature Reserve, southern Vietnam - Nguyen, Sang Ngoc; Nguyen, Luan Thanh; Nguyen, Vu Dang Hoang; Orlov, Nikolai L.; Murphy, Robert W. (Zootaxa, 2018)
A new forest skink of the genus Sphenomorphus Fitzinger, 1843 is described from Khanh Hoa Province, southern Vietnam based on morphological characters of four specimens and a fragment of 653 nucleotides of the gene COI. Sphenomorphus yersini sp. nov. is characterized by the following morphological characters: medium size in adults (snout-vent length up to 55 mm); tail length/snout-vent length ratio 1.81; toes reach to fingers when limbs adpressed; midbody scale rows 32–34, smooth; paravertebral scales 61–69; ventral scale rows 58–67; subcaudal scales 112; supraoculars four, rarely five; prefrontals in broad contact with one another; loreal scales two; tympanum deeply sunk; smooth lamellae beneath finger and toe IV 10–12 and 18–20 respectively; a pair of enlarged precloacal scales; hemipenis deeply forked and asymmetrical with two differently sized smooth lobes. The new species differs from its most similar congener, Sphenomorphus buenloicus Darevsky & Nguyen, 1983, by 16.4–16.7% uncorrected p-distance in COI sequences.